ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CADANGAN DEVISA(STUDI KASUS DI INDONESIA DAN CHINA) - Rini Mildyanti; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to determine the factors that influence foreign exchange reserves in Indonesia and China.The research type is descriptive research while the data used is time series data from 1987-2016 obtained from documentation of Bank Indonesia, BPS Indonesia, and International Monetary Fund (IMF). The results of this study indicate that : exchange rate and portfolio investment has a significant positive effect on foreign exchange reserve in Indonesia. Net export has a negatif and not significant effect on foreign exchange reserve in Indonesia. While, exchange rate has a negatif and not significant effect on foreign exchange reserve on China’s. Net export has a significant positive effect on foreign exchange reserve in China’s. While, portfolio investmen has a negative and significant effect on foreign exchange reserve.. Based on this research is expected to provide information about foreign exvhange reserve in Indonesia and China’s as well as the factors that influence,